2018
DOI: 10.1097/pcc.0000000000001547
|View full text |Cite
|
Sign up to set email alerts
|

Impressions of Early Mobilization of Critically Ill Children—Clinician, Patient, and Family Perspectives*

Abstract: Clinicians, patients, and families were highly supportive of mobilization in critically ill children; however, concerns were identified with respect to how and when to execute this practice. Understanding key stakeholder perspectives enables the development of strategies to facilitate the implementation of early mobilization and in-bed cycling, not just in the context of a clinical trial but also within the culture of practice in a PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(82 citation statements)
references
References 21 publications
4
74
0
3
Order By: Relevance
“…This highlights the importance of bedside nurse communication with families about mobilization therapies and is supported by other studies in which researchers examine collaboration between parents and staff during early mobilization. 17,29,30 Parent mobilization stress was correlated with parent preadmission and PICU-related stress. There is substantial morbidity for parents of children admitted to the PICU, including the development of not only parent stress but also PICS-p and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This highlights the importance of bedside nurse communication with families about mobilization therapies and is supported by other studies in which researchers examine collaboration between parents and staff during early mobilization. 17,29,30 Parent mobilization stress was correlated with parent preadmission and PICU-related stress. There is substantial morbidity for parents of children admitted to the PICU, including the development of not only parent stress but also PICS-p and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent qualitative study of families of critically ill children revealed that families support early mobilization, and researchers highlight the importance of family engagement in these therapies. 17 In our PICU, we have had a goal-directed earlymobilization protocol in place for .3 years and have found that parent refusal is a barrier to mobilization in 10% of cases in which barriers contributed to protocol failure. 18 Researchers in previous studies have also listed parent refusal as a barrier to mobilization, 17 although several barriers to improving early mobilization exist at both the patient and institutional levels.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The most common barriers to mobilizing children are lack of physiotherapy resources, lack of practice guidelines, and concerns for patient safety (14,16,24). In a recent publication by Zheng et al that conveys the results of post-mobilization interviews, both clinicians and parents expressed similar concerns that mobilization was not prioritized early in the ICU stay (25). Clinicians were primarily concerned for the safety of patients, whereas parents were more focused on prognosis of their child's illness.…”
Section: Early Mobilization: Definition Design and Implementationmentioning
confidence: 99%
“…Some barriers have been reported to the clinical condition of the patient, such as clinical instability; difficulty in the clinical diagnosis and the severity of the disease; risk of displacement of devices (eg catheters and intra-tracheal cannula); excessive and/or inadequate analgesia dosage; physical constraints; obesity; inadequate nutritional status; lack of motivation in some children to participate in EM activities; among others 3,4 . However, current studies [3][4][5][6] show that multi-professional performance and family involvement contribute to the positive outcomes of EM as well as to minimize the mobilization barriers of sick children.…”
Section: The Early Mobilization For Children In Pediatric Intensive Carementioning
confidence: 89%